Adenosine receptors: Modulators of lipid availability that are controlled by lipid levels. (June 2017) - Leiva, Andrea; Guzmán-Gutiérrez, Enrique; Contreras-Duarte, Susana; Fuenzalida, Bárbara; Cantin, Claudette; Carvajal, Lorena; Salsoso, Rocío; Gutiérrez, Jaime; Pardo, Fabián; Sobrevia, Luis
Abstract: Adenosine as well as agonists and antagonists for the four adenosine receptor subtypes (A1R, A2AR, A2BR and A3R) play a role in several key physiological and pathophysiological processes, including the regulation of vascular tone, thrombosis, immune response, inflammation, and angiogenesis. This review focuses on the adenosine-mediated regulation of lipid availability in the cell and in the systemic circulation as well in humans and animal models. Therefore, adenosine, mainly by acting on A1R, inhibits lipolysis activity, leading to reduction of the circulating fatty acid levels. This nucleoside can also participate in the early development of atherosclerosis by inhibiting the formation of foam cells via stimulation of cholesterol efflux through A2AR expressed on macrophages and reduction of the inflammatory process by activating A2AR and A2BR. Adenosine also appears to modulate intracellular cholesterol availability in Niemann-Pick type C1 disease and Alzheimer disease via A2AR and A3, respectively. Remarkably, the role of adenosine receptors in the regulation of plasma total cholesterol and triglyceride levels has been studied in animal models. Thus, an anti-atherogenic role for A2BR as well as a pro-atherogenic role of A2AR and A1 have been proposed; A3R has not been shown to participate in the control of lipid levels or the development of atherosclerosis. Surprisingly, and despite the role of A2A in the inhibition of foam cell formation among isolated cells, this receptor appears to be pro-atherogenic in mice. Remarkably, the role of adenosine receptors in human dyslipidaemia and atherosclerosis must to be elucidated. Additionally, it has been reported that increased lipid levels impair the effects of adenosine/adenosine receptors in controlling vascular tone, and we speculate on the possibility that this impairment could be due to alterations in the composition of the membrane microdomains where the adenosine receptors are located. Finally, a possible role for adenosine/adenosine receptors in the phenomena of dyslipidaemia in pregnancy has been proposed.